Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1515/zna-2020-0047
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational studies on optical properties of a promising N-benzylideneaniline derivative for non-linear optical applications

Abstract: A new organic non-centrosymmetric nonlinear optical (NLO) material, p-nitrobenzylidene-p-phenylamineaniline (PNBPDA) was synthesized and single crystals of PNBPDA were grown from ethanol solution by slow evaporation solution growth technique. Single crystal X-ray diffraction (XRD) and powder XRD data confirm that PNBPDA crystallizes in monoclinic system with non-centrosymmetric space group Cc.Various characterizations like PXRD, fourier transform infrared (FT-IR) spectroscopy, thermal analysis and micro hardne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Previous studies have reported that large PNPA crystals can be grown from chloroform and methanol mixtures via slow evaporation . Our additional studies demonstrate that crystal growth via slow evaporation from CH 2 Cl 2 provides the best quality crystals with the largest sizes.…”
Section: Methodssupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies have reported that large PNPA crystals can be grown from chloroform and methanol mixtures via slow evaporation . Our additional studies demonstrate that crystal growth via slow evaporation from CH 2 Cl 2 provides the best quality crystals with the largest sizes.…”
Section: Methodssupporting
confidence: 56%
“…Previous studies have reported that large PNPA crystals can be grown from chloroform and methanol mixtures via slow evaporation. 25 Our additional studies demonstrate that crystal growth via slow evaporation from CH 2 Cl 2 provides the best quality crystals with the largest sizes. In a typical slow evaporation experiment, 3.3 g of powdered (pure) PNPA was dissolved in 100 mL of CH 2 Cl 2 with heating and stirring until all solids are dissolved.…”
Section: ■ Introductionmentioning
confidence: 74%
“…The choice of solvent played a key factor for the growth of fair quality single crystals. [ 15 ] In order to identify the suitable solvent, solubility of ABAQ salt in different solvents of water and ethanol was determined. The solubility of ABAQ in water and ethanol was accessed as a function of temperature in the range of 30 and 65 °C.…”
Section: Methodsmentioning
confidence: 99%